Aturan Penggunaan Bahasa Indonesia Pada Label Yang Mencakup Informasi Suatu Produk - Jihan Sulistia Nabila; Rani Apriani (Legal Spirit, 2022)
The development of the times accompanied by technological advances makes it easy for consumers to fulfill their needs. Currently, consumers can easily and quickly obtain their needs in various marketplaces offered by business actors. Free trade in Indonesia causes many products from abroad to circulate in the community, many of which do not include information using Indonesian, so that the information obtained by consumers is not conveyed clearly, precisely, and completely. Whereas in meeting the needs of the community, they prefer to buy goods and services that are traded freely because the prices are relatively cheaper without thinking about the effects of goods and or services that are traded freely without permission from the Ministry of Health. The number of products on the market that have information that is not clear and complete, especially products from abroad which usually only include information using foreign languages only results in harm to consumers both materially and immaterially, because the information in a product is very important for consumers. as a consideration to see whether the product is in accordance with what is desired or needed and also whether the product is safe for use or consumption. Therefore, as a student, the writer is obliged to inform about the rights and obligations of consumers and business actors in carrying out trading activities, including in including information using Indonesian. Using the normative juridical method where we examine the laws and regulations related to this article. Thus, the use of Indonesian in information on a product is very important for consumers and must be carried out by business actors.